Mixing of Perfluorooctanesulfonic Acid (PFOS) Potassium Salt with Dipalmitoyl Phosphatidylcholine (DPPC) - Lehmler, H.-J. (2006)
Perfluorooctane-1-sulfonic acid (PFOS) is emerging as an important persistent environmental pollutant. To gain insight into the interaction of PFOS with biological systems, the mixing behavior of dipalmitoylphosphatidylcholine (DPPC) with PFOS was studied using differential scanning calorimetry (DSC) and fluorescence anisotropy measurements. In the DSC experiments the onset temperature of the DPPC pretransition (T(p)) decreased with increasing PFOS concentration, disappearing at X(DPPC) ≤ 0.97. The main DPPC phase transition temperature showed a depression and peak broadening with increasing mole fraction of PFOS in both the DSC and the fluorescence anisotropy studies. From the melting point depression in the fluorescence anisotropy studies, which was observed at a concentration as low as 10 mg/L, an apparent partition coefficient of K = 5.7 × 10(4) (mole fraction basis) was calculated. These results suggest that PFOS has a high tendency to partition into lipid bilayers. These direct PFOS-DPPC interactions are one possible mechanism by which PFOS may contribute to adverse effects, for example neonatal mortality, in laboratory studies and possibly in humans.